Feeding of Fermented Soybean Meal on Broiler Performance - Mathivanan, R.; Selvaraj, P.; Nanjappan, K. (International Journal of Poultry Science, 2006)
Soybean meal was fermented with Aspergillus niger for 48 h, dried and supplemented in the broiler diet at 0.5, 1.0 and 1.5 percent to study its effect on production performances and intestinal characteristics by using 200 day-old Vencob broilers for 6 weeks period and compared with control diet and commercial enzyme preparation. The result revealed that there was no difference in body weight between treatments up to 4th weeks of age. However, body weight of 0.5 percent FSM fed group was significantly (P< 0.05) higher than control at 5th and 6th weeks of age. The cumulative feed consumption was significantly (P< 0.05) lesser in 1.5 percent FSM group at 5th and 6th weeks of age. During 3rd and 4th weeks, 0.5 percent FSM fed group recorded better (P< 0.05) FCR than other groups. The livability was 100 percent in all the treatment groups. The percentage of intestine, pancreas, ready-to-cook weight to live weight, intestine length and viscosity of intestinal content were not significantly differed between the treatments. However, the pH of intestinal content was significantly (P< 0.05) lower in 0.5, 1.0 percent FSM and commercial enzyme supplemented groups as compared to control. The ileum villi length and width was significantly (P< 0.05) higher in 0.5, 1.0 FSM and commercial enzyme supplemented group compared to control. The activities of digestive enzymes did not differ significantly between treatments except lipase activity where, the lipase activity was significantly (P< 0.05) higher in 0.5 percent and 1.0 percent FSM than other groups. It was concluded that fermented soybean meal may be supplemented in broiler diet at 0.5 percent level as microbial enzyme supplement to improve the production performance of broilers.